1986
DOI: 10.1515/zna-1986-1110
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Investigations of the Low-Temperature Phases of the Organic Metals α- and β-(BEDT-TTF)2I3

Abstract: The structure of single crystals of the organic metals α- and β-(BEDT-TTF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 1 publication
2
30
0
Order By: Relevance
“…Even very small changes can seriously influence the superconducting transition. In the organic charge transfer-salt /?-(BEDT-TTF) 2 I 3 [BEDT-TTF = bis-(ethylenedithio)tetrathiofulvalene] below 195 K exists an incommensurate modulation [1] and below 125 K a commensurate superstructure with a pronounced distortion of the Ijanions [2], Under ambient pressure the superconducting transition temperature T c is 1.3 K [3] but after a particular pressure-temperature cycling procedure superconductivity can be stabilized at ambient pressure even at r c =8.1 K [4], A recent neutron diffraction study has shown that the high-r c superconducting phase of /?-(BEDT-TTF) 2 I 3 is completely ordered [5] showing that during the pressure-temperature cycling procedure the distortion of the Ij-anions in /?-(BEDT-TTF) 2 I 3 is suppressed resulting in an increase of T c . The IJ-anions and other polyhalide ions used in organic superconductors are sensitive to distortions and slight changes in the crystal.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even very small changes can seriously influence the superconducting transition. In the organic charge transfer-salt /?-(BEDT-TTF) 2 I 3 [BEDT-TTF = bis-(ethylenedithio)tetrathiofulvalene] below 195 K exists an incommensurate modulation [1] and below 125 K a commensurate superstructure with a pronounced distortion of the Ijanions [2], Under ambient pressure the superconducting transition temperature T c is 1.3 K [3] but after a particular pressure-temperature cycling procedure superconductivity can be stabilized at ambient pressure even at r c =8.1 K [4], A recent neutron diffraction study has shown that the high-r c superconducting phase of /?-(BEDT-TTF) 2 I 3 is completely ordered [5] showing that during the pressure-temperature cycling procedure the distortion of the Ij-anions in /?-(BEDT-TTF) 2 I 3 is suppressed resulting in an increase of T c . The IJ-anions and other polyhalide ions used in organic superconductors are sensitive to distortions and slight changes in the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…In contradiction to the geometry of the Ij-anions in ß-(BEDT-TTF) 2 I 3 below 125 K the (IAuI)"-anions in /?-(BEDT-DDT) 2 IAUI are linear and symmetric in the whole temperature range below 300 K [7]. The structure of /?-(BEDT-TTF) 2 IAuI is completely ordered.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations